Q EXTRACTION USING S-TRANSFORM - ZAIN AMIRUDDIN (NIM 12403018), AHMAD
S-transform provides time-frequency representation from signal. The advantage of this transformation is the ability to increase resolution in time domain by choose appropriate gaussian window. The estimation of interval Q get by comparing ratio frequency amplitude of wavelet on second and first event. This method called spectral ratio. The objective of this study is confirmation of extraction Q interval. So, at first, seismic traces synthetic that has interval Q value is needed. To build those traces is used attenuation operator that called Q impulse response. By using spectral ratio method Q value can extraction. Then, these results compared to input interval Q model. For thick layer case Q interval are stabile. For thin layer case Q interval can be still estimated and depended on width of gaussian window.